Acute Obstruction of a Chronic Organoaxial Gastric Volvulus Detected on Blood Pool Imaging of a Bone Scan. (December 2015) - Bryanton, Mark; Mujoomdar, Amol; Rachinsky, Irina
Abstract : Abstract: Acute obstruction of a chronic gastric volvulus was incidentally detected on blood pool imaging of a total body bone scan performed for an elevated prostate-specific antigen level. The patient had been diagnosed with an organoaxial gastric volvulus within a paraesophageal hernia 4.5 years previously, with no evidence for obstruction. The patient remained asymptomatic until becoming acutely obstructed on the day of his bone scan. This case gives further evidence for the additive utility of routine total body blood pool imaging for detecting and characterizing both osseous and nonosseous pathology.